Fluggastkontrollstellen im Wandel. - Süß, Nicole (Deutscher Verkehrs-Verl., 2008)
Die Fluggastkontrollstellen - das Nadelöhr am Boden und somit wichtiger Bestandteil der Prozesskette - unterliegen dem Wandel, um auch künftigem Passagierwachstum effizient und kostengünstig gewachsen zu sein.

Rising numbers of air travellers, and the ongoing quest for more sophisticated passenger security check facilities, tend to make the control procedure more complex. In order to avoid decreases in passenger throughput numbers, and a potential reduction in the journey time advantage associated with air travel, the Federal Ministry of the Interior (BMI) in June 2004 entrusted the project "Increased throughput speed at airport security-checkpoints" to a team of specialists from Fraport, the Federal Police Agency of Frankfurt airport and Lufthansa. The team discovered the advantage of running certain security checks in parallel (preparing airline passengers in advance, arranging for secondary passenger and hand baggage checks and baggage hand-over). The new airline passenger security control concept 'iLane.one' has led to significant increases in passenger throughput rates while, in turn, positively affecting the air transport security check fees, which passengers have to pay for.
Airline passenger security checkpoints undergoing change.
Keywords: Verkehr; Luftverkehr; Sicherheitsmaßnahme; Flughafen; Leistungsfähigkeit; Luftsicherheit; Kontrolle; Passagier; Fluggast; Gepäck; Gefahrstoff